Civil War Risk in Democratic and Non-Democratic Neighborhoods - Raleigh, Clionadh (World Bank, Washington, DC, 2012)
This study questions the extent to which domestic conflict is influenced by national, regional, and international relationships. It is designed to answer specific questions relating to the effects of neighboring characteristics on a state's risk of conflict and instability: What is the interaction between neighboring conflict and political disorder? Do democratic neighborhoods have different conflict trajectories than non-democratic neighborhoods and if so, where and why? Given that most poor countries are located in poor and conflictual neighborhoods, to what extent is there a relationship between poverty and political disorder in different regime neighborhoods? Using spatial lag terms to specify neighboring regime characteristics and multilevel models to differentiate between explanatory levels, this study reiterates the importance of domestic and neighboring factors in promoting or diminishing the risk of instability and conflict. However, the pronounced negative effects of autocratic and anocratic neighborhoods are mitigated by a growing domestic GDP. This study also finds that democratic neighborhoods are more stable, regardless of income level. Research presented here is unique in its contribution on how regime type is a significant development indicator, which in turn is salient in determining the risks of civil war across states.